Elevated Levels of Prothrombin Activation Fragment 1+2 in Plasma from Patients with Heterozygous Arg506 to Gin Mutation in the Factor V Gene (APC-Resistance) and/or Inherited Protein S Deficiency - Zöller, Benget; Holm, Johan; Svensson, Peter; Dahlbäck, Björn (Thrombosis and Haemostasis, 1996)
Inherited resistance to activated protein C (APC-resistance), caused by a point mutation in the factor V gene leading to replacement of Arg(R)506 with a Gin (Q), and inherited protein S deficiency are associated with functional impairment of the protein C anticoagulant system, yielding lifelong hypercoagulability and increased risk of thrombosis. APC-resistance is often an additional genetic risk factor in thrombosis-prone protein S deficient families. The plasma concentration of prothrombin fragment 1+2 (F1+2), which is a marker of hyper-coagulable states, was measured in 205 members of 34 thrombosis-prone families harbouring the Arg506 to Gin mutation (APC-resistance) and/or inherited protein S deficiency. The plasma concentration of F1+2 was significantly higher both in 38 individuals carrying the FV:Q506 mutation in heterozygous state (1.7 ± 0.7 nM; mean ± SD) and in 48 protein S deficient cases (1.9 ± 0.9 nM), than in 100 unaffected relatives (1.3 ±0.5 nM). Warfarin therapy decreased the F1+2 levels, even in those four patients who had combined defects (0.5 ± 0.3 nM). Our results agree with the hypothesis that individuals with APC-resistance or protein S deficiency have an imbalance between pro- and anti-coagulant forces leading to increased thrombin generation and a hypercoagulable state.